Behavior staff of the Covid-19 Vaccine in UMKT - Sri Sunarti (Jurnal Kesehatan Masyarakat Indonesia, 2022)
Background: Background: The implementation of the Covid-19 vaccination is an important strategy for the current government as an effort to prioritize the health and safety of the citizens of the education unit, to accelerate the implementation of limited PTM. If there are educators or education personnel who have not been vaccinated against Covid-19, it is advisable to provide PJJ services from home. Objective: To determine the behavior of the Covid-19 vaccine in UMKT education staff. Methods: This type of research is descriptive research. Data was obtained by filling out an online questionnaire (google form). The number of research samples was 56 using the Simple Random Sampling technique. Results: The results showed that knowledge was good 94.6%, positive attitude was 87.5%, family environment supported vaccine behavior 91.1%, and services provided were satisfied at 67, 9% Conclusion: Behavioral factors for vaccinating, namely the family environment, knowledge, attitudes, and services for the implementation of the Covid-19 Vaccine for Education Personnel at UMKT are all good and satisfied with the service, in addition to the above, the behavior of the vaccine is due to the regulation that to do WFO (Work from Office) as an educational staff, one of the requirements for vaccines is to vaccinate. So it is necessary to socialize about vaccines and conduct health education about the Covid-19 vaccine